Pharmacological and computational evaluation of fig for therapeutic potential in hyperactive gastrointestinal disorders - Muhammad Bilal Riaz; Arif-ullah Khan; Neelam Gul Qazi (BMC, 2019)
Abstract Background Ficus palmata (Fig), are distributed in different parts of the world, and are used in traditional medicine to treat various ailments including inflammation, tumor, epilepsy, jaundice, influenza and bacillary dysentery. The present study aimed to evaluate the antidiarrheal, antisecretary, antispasmodic, antiulcer and anti motility properties of Ficus palmata. Methods In-vivo, in-vitro and in-silico techniques were used to investigate various gastrointestinal effects of Ficus palmata. Antidiarrheal, antisecretary, antispasmodic, antiulcer, anti motility and molecular docking were performed using castor oil induced diarrhea and fluid accumulation, isolated tissue preparations, ethanol-HCl induced ulcer assay, charcoal meal transit time and Auto Doc Vina. Results Ficus palmata crude extract (Fp.Cr) exhibited protection against castor oil-induced diarrhea in mice and dose-dependently inhibited intestinal fluid secretions. Fp.Cr caused relaxation of spontaneous and K+ (80 Mm)-induced contractions in isolated rabbit jejunum preparations. It showed protective effect against gastric ulcers induced by ethanol-hydrochloric acid in rats. Fp.Cr reduced distance travelled by charcoal meal in the gastrointestinal transit model in mice. The plant constituents: psoralenoside and bergapten showed high binding affinities (E-value ≥ − 6.5 Kcal/mol) against histaminergic H1, calmodulin and voltage gated L-type calcium channels, while showed moderate affinities (E-value ≥7 Kcal/mol) against dopaminergic D2, adrenergic α1, muscranic M3, mu-opioid, whereas revealed lower affinities (E-value ≥9.5 Kcal/mol) vs. muscranic M1, histaminergic H2 and H+/K+ ATPase pump. Germanicol acetate and psoralene exhibited weak affinities against aforementioned targets. Conclusion This study reveals that Ficus palmata possesses anti-diarrheal, anti-secretory, anti-spasmodic, anti-motility and anti-ulcer activities. The various constituents reveal different binding affinities against target proteins, which mediate the gastrointestinal functions.